NILAI-NILAI PENDIDIKAN MULTIKULKTURAL DALAM KEHIDUPAN ANTAR UMAT BERAGAMA DI DESA SINDANG JATI KECAMATAN SINDANG KELINGI - Muhammad Irsyad Fadhila; Ngadri Yuroso; Eka Yanuarti (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2020)
Multicultural education is education that prioritizes an education that has a high tolerance value and this multicultural education is the right and appropriate step to be implemented, especially in our country, Indonesia considering that Indonesia is a country that has a variety of cultures, races, ethnicities, and religions, for creating harmony in social life, multicultural education is very appropriate to be applied. The purpose of this multicultural education is to form an attitude of mutual acceptance, mutual respect both in terms of values and culture of each other's beliefs. With this multicultural education, it is hoped that humans can expand humans to defeat selfishness, namely the attitude of someone who tends to expect other people like himself.The purpose of this study is to first find out first how the values of multicultural educational insights in the life of interfaith people in Sindang Jati Village, the second to find out the supporting factors of religious harmony. This type of research is field research using a qualitative approach, the source of data is the Village Head, Religious figures namely Islam, Buddhism, and Catholicism. Data collection techniques using observation, interviews, and documentation.The results showed: first, the values of multicultural education insight in inter-religious life in Sindang Jati, including the values of democracy, equality, and justice; human values, togetherness, and peace, as well as social attitudes, namely: recognition, acceptance, and respect for others, such as mutual respect when worshiping and implementing a justice system in maintaining security and order. The two factors supporting religious harmony in the village of Sindang Jati include humanity, togetherness, and peace, and social attitudes, namely: recognition, acceptance, and respect for other people who are high, such as respecting when other religious communities worship, maintaining security and order of citizens regardless of religious differences such as the presence of patrol posts.